Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Berdasarkan Prosedur Newman - Aan Nurhasanah; Siti Aisah; Rahayu Syafari (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2021)
This study aims to describe mistakes made by students in solving math story problems on the KPK and FPB materials based on Newman’s prosedures in grade IV elementary school in Salado  district. In this study, the types of errors made by students were analyzed based on Newman’s theory of procedures and the causes of errors. The approach in this study uses a qualitative approach with a case study method. Data collection techniques used are documentation studies and interviews. Based on the results of the study, it can be concluded that the types of errors that arise when students solve KPK and FPB story problems are: (1) reading errors, (2) reading comprehension, (3) transformation errors, (4) process skill, (5) encoding errors. The factors that cause students make mistakes are: a) the lack of students ability to read; b) students have difficulty understanding the questions; c) students forget to write down the information that is known and asked; d) do not understand the concepts of KPK and FPB; e) errors in the previous stage; f) lack of accuracy of students in writing the calculation process; and g) students forget to the write down the conclusion of the answer.